THE RHETORIC OF LEADERSHIP: Deepening Responsible Autonomous Agency and Broadening the Scope of Participation through an Ignatian Contemplation of the Parable of the Good Shepherd - Rixon, Gordon (Science et Esprit, 2022)
The contentions of meaning implicit in the metaphors and symbols of the Good Shepherd Parable bear upon leadership issues and highlight the ambiguities, paradoxes, and conflicts of self-transcending social, cultural, and religious projects. Both shepherds and sheep need metaphors to stretch their understanding and engagement and symbols to reach toward a guiding vision that remains beyond their grasp. The Ignatian appropriation of the medieval monastic adaptation of principles of Ciceronian rhetoric in the practice of mental prayer helps to resolve, discern, cultivate, and direct the use of self in the service of such visionary projects. Ignatian discernment contributes to such dynamic development by identifying and resolving the norming affective dispositions of gratitude for creaturehood, freedom in the use of gifts and talents, and commitment to praise, reverence, and serve God and neighbor. These dispositions affirm human agency and orient practitioners to purposeful action without certainty about present facts and future outcomes. Such healing of human agency and participation in a higher purpose contributes to the restoration and elevation of human history.